Exercise-Induced Bronchospasm and Allergy - Serena Caggiano; Serena Caggiano; Renato Cutrera; Renato Cutrera; Antonio Di Marco; Antonio Di Marco; Attilio Turchetta (Frontiers Media S.A., 2017)
Sport is an essential part of childhood, with precious and acknowledged positive health effects but the impact of exercise-induced bronchoconstriction (EIB) significantly reduces participation in physical activity. It is important to recognize EIB, differentiating EIB with or without asthma if the transient narrowing of the airways after exercise is associated with asthmatic symptoms or not, in the way to select the most appropriate treatment among the many treatment options available today. Therapy is prescribed based on symptoms severity but diagnosis of EIB is established by changes in lung function provoked by exercise evaluating by direct and indirect tests. Sometimes, in younger children it is difficult to obtain the registration of difference between the preexercise forced expiratory volume in the first second (FEV1) value and the lowest FEV1 value recorded within 30 min after exercise, defined as the gold standard, but interrupter resistance, in association with spirometry, has been showed to be a valid alternative in preschool age. Atopy is the main risk factor, as demonstrated by epidemiologic data showing that among the estimated pediatric population with EIB up to 40% of them have allergic rhinitis and 30% of these patients may develop adult asthma, according with atopic march. Adopting the right treatment and prevention, selecting sports with no marked hyperventilation and excessive cooling of the airways, children with EIB can be able to take part in physical activity like all others.